Bacterial Ghosts-Based Vaccine and Drug Delivery Systems - Chen, Haojie; Ji, Hao; Kong, Xiangjun; Lei, Pengyu; Yang, Qinsi; Wu, Wei; Jin, Libo; Sun, Da (Pharmaceutics, 2021)
Bacterial ghosts (BGs) are empty bacterial envelopes of Gram-negative bacteria produced by controlled expressions of cloned gene E, forming a lysis tunnel structure within the envelope of the living bacteria. Globally, BGs have been used as vaccine delivery systems and vaccine adjuvants. There is an increasing interest in the development of novel delivery systems that are based on BGs for biomedical applications. Due to intact reservation of bacterial cell membranes, BGs have an inherent immunogenicity, which enables targeted drug delivery and controlled release. As carrier vehicles, BGs protect drugs from interference by external factors. In recent years, there has been an increasing interest in BG-based delivery systems against tumors, inflammation, and infection, among others. Herein, we reviewed the preparation methods for BGs, interactions between BGs and the host, and further highlighted research progress in BG development.